Less frequent but equally useful: social and temporal comparisons in light of mindfulness and self-compassion - Borgdorf, Kira Skirwitt Ann; Küchler, Gabriela; Wrzus, Cornelia; Aguilar-Raab, Corina (Mindfulness, 2024)
Objectives Social and temporal comparisons are ubiquitous and considered important sources of an individual’s self-knowledge. Yet, comparisons are inherently evaluative and may result in negative affective consequences. In contrast, mindfulness and self-compassion are characterized by a present-moment, non-evaluative, and accepting stance toward the self and one’s experiences and are associated with numerous positive psychological health indicators. This study innovatively examined the associations of mindfulness and self-compassion with frequency and perceived utility of social (i.e., with others) and past-temporal (i.e., with the past self) comparisons across different life domains. Method In a binational online study, we examined the associations between mindfulness, self-compassion, and comparisons across five different domains (i.e., extraversion, emotional stability, appearance, professional success, and private life) in a gender- and age-diverse sample at two measurement points 6 months apart (NT1 = 615, NT2 = 310, 18-84 years, 51.5% female). Results Results of multiple regression analyses indicated that the more mindful or self-compassionate individuals were, the less they compared themselves with others or their past self (across domains β =  − 0.25 to − 0.51; all p-values < 0.001). Contrary to our expectations, the overall pattern of results suggests that mindfulness and self-compassion were generally not significantly associated with perceiving comparisons as less useful (after family-wise error correction; β =  − 0.04 to − 0.14; all p-values ≥ 0.008). Conclusions The findings suggest that comparisons, when done mindfully and self-compassionately, can be a valuable source of information for self-knowledge. At the same time, mindfulness and self-compassion may buffer against negative affective outcomes of comparison processes. Preregistration This study is preregistered on the Open Science Framework: https://osf.io/6hfb2 .